Trk receptor signaling and sensory neuron fate are perturbed in human neuropathy caused by Gars mutations - Sleigh, J; Dawes, J; West, S; Wei, N; Spaulding, E; Gómez-Martín, A; Zhang, Q; Burgess, R; Cader, M; Talbot, K; Yang, X; Bennett, D; et al. (National Academy of Sciences, 2017)
Charcot-Marie-Tooth disease type 2D (CMT2D) is a peripheral nerve disorder caused by dominant, toxic, gain-of-function mutations in the widely expressed, housekeeping gene, GARS The mechanisms underlying selective nerve pathology in CMT2D remain unresolved, as does the cause of the mild-to-moderate sensory involvement that distinguishes CMT2D from the allelic disorder distal spinal muscular atrophy type V. To elucidate the mechanism responsible for the underlying afferent nerve pathology, we examined the sensory nervous system of CMT2D mice. We show that the equilibrium between functional subtypes of sensory neuron in dorsal root ganglia is distorted by Gars mutations, leading to sensory defects in peripheral tissues and correlating with overall disease severity. CMT2D mice display changes in sensory behavior concordant with the afferent imbalance, which is present at birth and nonprogressive, indicating that sensory neuron identity is prenatally perturbed and that a critical developmental insult is key to the afferent pathology. Through in vitro experiments, mutant, but not wild-type, GlyRS was shown to aberrantly interact with the Trk receptors and cause misactivation of Trk signaling, which is essential for sensory neuron differentiation and development. Together, this work suggests that both neurodevelopmental and neurodegenerative mechanisms contribute to CMT2D pathogenesis, and thus has profound implications for the timing of future therapeutic treatments.